2018
DOI: 10.1111/sjtg.12232
|View full text |Cite
|
Sign up to set email alerts
|

Whose knowledge matters in climate change adaptation? Perceived and measured rainfall trends during the last half century in south‐western Tanzania

Abstract: Parts of eastern Africa have experienced substantial climatic variability and extremes during the last few decades. Here we explore the extent to which local place‐based knowledge is used and is relevant to understanding and appropriately responding to place‐based climate variability and change (specifically rainfall) in an area of considerable rainfall variability in south‐western Tanzania. Primary data were collected using focus group discussions and household questionnaire surveys, and secondary data obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…An increase in extreme droughts was not identified in previous studies on Mount Kilimanjaro, although it was cited in the Pare and Udzungwa Mountains. An increase in wind strength during the rainy season was previously mentioned in the Pare Mountains [64], but not on Mount Kilimanjaro and the Udzungwa Mountains. While our study participants in both mountains reported important changes in fog, only one previous study recorded this change in the East Usambaras [66].…”
Section: Climatic Changes and Impactsmentioning
confidence: 66%
See 1 more Smart Citation
“…An increase in extreme droughts was not identified in previous studies on Mount Kilimanjaro, although it was cited in the Pare and Udzungwa Mountains. An increase in wind strength during the rainy season was previously mentioned in the Pare Mountains [64], but not on Mount Kilimanjaro and the Udzungwa Mountains. While our study participants in both mountains reported important changes in fog, only one previous study recorded this change in the East Usambaras [66].…”
Section: Climatic Changes and Impactsmentioning
confidence: 66%
“…However, in the Udzungwa Mountains, the early onset of the rainy season was noted instead of a later onset of rainfall-which we report here. Decreased stream flow was previously reported in both mountains [27,45,59,61,64,65]. An increase in extreme droughts was not identified in previous studies on Mount Kilimanjaro, although it was cited in the Pare and Udzungwa Mountains.…”
Section: Climatic Changes and Impactsmentioning
confidence: 81%
“…According to them, it resulted in a shortage of food, a decrease in income, youth emigration, increased disease outbreaks, and increased cost of food. A similar situation was also noted in the Great Ruaha River sub-basin that the shift in rainfall onset affected the normal growth of crops leading to reduced crop yield to the extent that farmers faced food insecurity (Pauline et al, 2017;Pauline and Grab, 2018). Likewise, Ndaki (2014) in his study of CC adaptation strategies at Mkomazi sub-catchment found similar results regarding out-migration.…”
Section: Discussionmentioning
confidence: 52%
“…Also, the study of Magreth and Bushesha (2017) on the potential of forest resources on adaptation to CCV in the Kilindi District revealed that farmers perceived that CC has prolonged droughts and shifts in rainfall patterns. Similar perceptions have been given by farmers in the Great Ruaha sub-basin: rainfall pattern is fluctuating and temperature increases (Pauline et al, 2017, Pauline andGrab, 2018). Likewise, farmers perceived that CC affects agriculture, forestry components, other environment components, and household livelihoods.…”
Section: Discussionmentioning
confidence: 55%
“…Local farmers indicate how weather patterns, such as delays to the start of rainfall, rainfall fluctuation and reduction before the growing season ends affects their cropping activities. Pauline and Grab () study various changes associated with the frequency, intensity and consistency of rainfall during the period 1960 to 2014 in south‐western Tanzania. Their study reveals how smallholder farmers in the Great Ruaha River Sub‐Basin rely on incremental adaptations of agricultural practices, in response to climatic stresses which have long‐term implications.…”
mentioning
confidence: 99%